2012
DOI: 10.3892/ijo.2012.1562
|View full text |Cite
|
Sign up to set email alerts
|

Genomic CGH-assessed structural DNA alterations in rectal carcinoma as related to local recurrence following primary operation for cure

Abstract: Abstract. Several factors determine overall outcome and possible local recurrence after curative surgery for rectal carcinoma. Surgical performance is usually believed to be the most pertinent factor, followed by adjuvant oncological treatment and tumor histopathology. However, chromosomal instability is common in colorectal cancer and tumor clones are assumed to differ in aggressiveness and potential of causing local recurrence. The aim of this study was, therefore, to evaluate if genetic alterations in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Well-known colon cancer alterations were also evaluated with Q-PCR; 1 region at chromosome 13 and 1 region at chromosome 20 as well as 1 region at chromosome 10 that is known to be unaffected in colorectal cancer (control) in DNA from tumour tissue biopsies. Primers were designed by TATAA Biocenter AB (Gothenburg, Sweden) with PrimerBlast (http://www.ncbi.nlm.nih.gov/tools/primer-blast/), primer sequences for chromosome 10, 13 and 20 are described elsewhere [10] and for chromosome 19 in Additional file 1: Table S1. The Q-PCR assays were validated on gBlocks to estimate the PCR efficiency of the assay.…”
Section: Methodsmentioning
confidence: 99%
“…Well-known colon cancer alterations were also evaluated with Q-PCR; 1 region at chromosome 13 and 1 region at chromosome 20 as well as 1 region at chromosome 10 that is known to be unaffected in colorectal cancer (control) in DNA from tumour tissue biopsies. Primers were designed by TATAA Biocenter AB (Gothenburg, Sweden) with PrimerBlast (http://www.ncbi.nlm.nih.gov/tools/primer-blast/), primer sequences for chromosome 10, 13 and 20 are described elsewhere [10] and for chromosome 19 in Additional file 1: Table S1. The Q-PCR assays were validated on gBlocks to estimate the PCR efficiency of the assay.…”
Section: Methodsmentioning
confidence: 99%
“…Losses of both chromosome arms 8p and 18q had a statistically significant negative effect on disease-free survival [6]. Kodeda et al showed that gain of 4q31.1-q31.22 was associated with local recurrence after primary operation and 22 affected genes of this region had high relevance to tumor biology such as p53 regulation and cell cycle activity [7]. A study comparing the genomic profiling between tumor specimens and the corresponding pulmonary metastases showed that loss at chromosome arm 5q had difference in frequency in two groups [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that abnormalities in Impact of chromosome 17q deletion in the primary lesion of colorectal cancer on liver metastasis gene and genomic copy numbers that contribute to lymph node metastases may be identified by comparative genomic hybridization (CGH) (13,14). It is expected that identification of specific gene and genomic variations may be used in the clinic as tumor markers and prognostic predictive factors for metastasis (12,15); these prognostic markers may serve as important tools for colorectal cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, targeted cancer therapies have been developed and approved for use in treating various types of cancer, and in certain therapies, treatment efficacy may be predicted by analyzing the gene variation of the primary lesion (11,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation